Wayang Art as a Media for Islamic Education for Early Children in the Midst of Globalization (Current Research in Education: Conference Series Journal, 2024)
The implementation of wayang is rarely preserved due to the impact of globalization and the rise of foreign culture that replaces local traditions. As an urgency to preserve cultural values and implement Islamic education for early childhood, this research aims to determine whether cultural preservation in implementing Islamic religious education can be achieved through the learning medium of Wayang. The method used in this research is a literature review, collecting information related to the topic. This data collection uses the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method. The data collection stage involved analyzing journal articles and summarizing the research objectives. The results show that using shadow puppet learning media effectively introduces Islamic education to young children. Shadow puppet media can instill morals and serve as role models for students, helping shape their character. Using wayang as a teaching tool can foster interest, engagement, enthusiasm, and learning motivation.